2020
DOI: 10.3390/vaccines8020247
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Basis of Genesis of Hepatocellular Carcinoma: Unique Challenges and Potential Opportunities through Immunomodulation

Abstract: A majority of hepatocellular carcinoma (HCC) develops in the setting of persistent chronic inflammation as immunological mechanisms have been shown to play a vital role in the initiation, growth and progression of tumours. The index review has been intended to highlight ongoing immunological changes in the hepatic parenchyma responsible for the genesis and progression of HCC. The in-situ vaccine effect of radiofrequency (RF) is through generation tumour-associated antigens (TAAs), following necrosis and apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 91 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…Numerous studies have demonstrated that the infiltration of tumor-associated immune cells and immune-related genes is correlated with the development and prognosis of HCC ( Duan et al, 2019 ; Huang et al, 2020 ; Tang et al, 2020 ). Remarkably, targeting on these immune cells and/or genes has been a prospective workable approach in HCC therapy ( Jayant et al, 2020 ). In this study, we attempted to explore the relationship between the mRNA expression of hub genes and immune cell infiltration using TIMER2.0.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated that the infiltration of tumor-associated immune cells and immune-related genes is correlated with the development and prognosis of HCC ( Duan et al, 2019 ; Huang et al, 2020 ; Tang et al, 2020 ). Remarkably, targeting on these immune cells and/or genes has been a prospective workable approach in HCC therapy ( Jayant et al, 2020 ). In this study, we attempted to explore the relationship between the mRNA expression of hub genes and immune cell infiltration using TIMER2.0.…”
Section: Resultsmentioning
confidence: 99%
“…The shift in the immune response from anti-tumor status to tumor tolerance contributes to the development and progression of HCC (Zamarron and Chen, 2011). Immune cells and immune-related genes have been reported as novel prognosis biomarkers and therapeutic targets for HCC (Jayant et al, 2020;Zhang et al, 2020). In this study, we aimed to construct a novel immune-related eRNA prognostic signature of HCC, and to characterize the eRNA signature as a useful prognostic tool and to identify therapeutic targets for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…eRNAs have been found to be an important regulators of the immune response, and are involved in a mutiple tumorigenic signaling pathways, such as p53, PPARr, and immune checkpoints (Melo et al, 2013;Jayant et al, 2020), which are closely related to malignancy formation and progression. In this study, we constructed a five-gene IReRS as a new prognostic model and validated its predictive utility.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, in the liver, large quantities of innate and adaptive immune cells play a critical role in immune surveillance to detect and eliminate pathogens and participate in immune response and regulation of host defenses. 8 However, the inflammatory state, due to risk factors that contribute to HCC, such as chronic infection with hepatitis B virus or hepatitis C virus, will change the tumor microenvironment and facilitate evasion of immune surveillance, leading to tumor tolerance and promoting the development of HCC. 8 Hence, targeted immunotherapy is actively researched with the goal of inhibiting aberrant oncogenic pathways and improving prognosis.…”
Section: Introductionmentioning
confidence: 99%